2013
DOI: 10.3109/08941939.2012.733487
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rabeprazole on LES Tone in Experimental Rat Model

Abstract: In the present study, rabeprazole caused no direct significant change in LES tone in the therapeutic dose range applied to the organ bath. However, rabeprazole at the high dose caused a significant decrease in the LES tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Relexant or inhibitory effects of PPIs at high doses were demonstrated on vascular precontracted smooth muscle, gallbladder, prostate, corpus cavernosum, myometrium, and lower esophageal sphincter. [1][2][3][4][5][6][7] Therefore, in our study, we conducted the experiment from concentration of 10 −6 M, which is actually about the Cmax of rabeprazole after single oral dosage of 20 mg, to 10 −3 M. 23 The pathophysiological mechanism of these effects has yet to be identified but the most popular proposed model is the inhibition of voltage operated Ca 2+ channels. In this study, we planned to observe the dose dependent effects of rabeprazole on the pylorus tone in the isolated human pylorus preparations, independent from any stimulation by acidity, paracrine hormones, and vagus nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relexant or inhibitory effects of PPIs at high doses were demonstrated on vascular precontracted smooth muscle, gallbladder, prostate, corpus cavernosum, myometrium, and lower esophageal sphincter. [1][2][3][4][5][6][7] Therefore, in our study, we conducted the experiment from concentration of 10 −6 M, which is actually about the Cmax of rabeprazole after single oral dosage of 20 mg, to 10 −3 M. 23 The pathophysiological mechanism of these effects has yet to be identified but the most popular proposed model is the inhibition of voltage operated Ca 2+ channels. In this study, we planned to observe the dose dependent effects of rabeprazole on the pylorus tone in the isolated human pylorus preparations, independent from any stimulation by acidity, paracrine hormones, and vagus nerve.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Two other studies, conducted after these previous studies, have shown that PPIs may also induce smooth muscle relaxation in lower esophageal sphincter in rat models. 6,7 The effects of PPIs, which are commonly used in treatment of gastritis, gastric ulcer, and gastroesophageal reflux disease on pylorus, have yet to be investigated. Pylorus is the most important control mechanism of the flow between the stomach and the intestines.…”
Section: Introductionmentioning
confidence: 99%
“…GERD conventional therapy involves the use of anti-secretory drugs such as proton pump inhibitors (PPI) and H2 receptor antagonists (HsRA) [16,17]. Despite of PPI efficacy to treat GERD, there is still a substantial group of cases (≈40% in some studies) who do not experience symptom relief with a standard PPI dose, due to transient lower esophageal sphincter relaxations, sensitivity to weakly acidic and/ or alkaline reflux, large volume of reflux and/or esophageal hypersensitivity [18][19][20].…”
Section: Introductionmentioning
confidence: 99%